Skrivnostni tujec in demonski sovražnik Drugi in drugost v slovenski slovstveni folklori - Mlakar, Anja (Studia Mythologica Slavica Supplementa, 2019)
Presented are the perceptions of different foreigners who came to Slovene lands in the past or in the present time, as shown in Slovene folk narratives. Despite often stereotyped picture of the Others, the research demonstrates an immense complexity of these narratives and the fact that they tell more about Us than about Them. The book ('The Mysteriou Stranger and the Demonic Enemy. "The Other" and Otherness in Slovene Folk Narratives') brings a theoretical overview of the current research on otherness in folklore studies and contextualizes the examples into a wider international folkloristic, anthropological and historical frames. Stories about the Turks, the Napoleon's French and the Huns reflect an interweaving of historical facts, archetypical imageries of the dangerous Foreigner and ideological influences. These narratives are strongly embedded into the landscape and reinforce the sense of a common identity of its members. The imagery of historic aggressors is understandably quite different from the imagery of Jews and the Roma, with whom the people of the Slovene lands have had a completely different kind of contact.The same goes for contemporary foreigners from other countries. Nevertheless, they all display a high level of stereotypization, generalization and projection of fears upon "the Other".